PENGARUH PENYAKIT INFEKSI DAN FAKTOR LINGKUNGAN TERHADAP STATUS GIZI BALITA DI KABUPATEN BANYUMAS - Erna Kusumawati; Dwi Sarwani Sri Rejeki (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Children under five years are risk group of infectious diseases and their health condition. Nutritional status in people in some area is determining by growth status especially related with childen under five years nutritional status. The aim of this research is to analize the influence of infectious disease and environtmental factors toward children under five years nutritional status in hte district of Banyumas. It is case control study design with retrospective approach with 69 children under five as sample. It used observational by using structured questionare to collecting the data from mother as research subject. Research variables such as children under five years nutrition status, infectious diseases, energy and protein consumption level, environmental level, environmental factors, sosio culture. Data is analyzed with univariate, bivariate and multivariate by using logistic regression. Research result showed that variable statistically signification influenced children under five nutritional status were energy consumption level, housing ventilation and housing cleaness. The effort to increase nutrional status among children under five years need a comprehensip program including increasing children under five consumption, healthy housing and increasing knowledge of mother about nutrition and health.